Perbedaan Pukulan Lob Berpola dan Pemberian Lob Tak Langsung Terhadap Ketepatan Pukulan Lob Dalam Permainan Bulutangkis Pada Atlet Pemula Putra PB. Lindu Aji Ngaliyan - Muhammad Shofiana (Journal of Physical Activity and Sports (JPAS), 2021)
Abstract Muhammad Shofiana "The difference between patterned lob and indirect lob is the accuracy of lob strokes in badminton games for young male athletes PB. Lidu Aji Ngaliyan ”Faculty of Social Sciences and Sports Education, PGRI University Semarang, 2020. The problems in this study were (1) whether there was a difference in the effect of patterned lob training and indirect lob treatment on the accuracy of lob strokes and (2) which one was better between patterned lob training and indirect lob practice. While the objectives of this study were (1) to determine the effect of patterned lob training and indirect lob on the accuracy of lob stroke accuracy (2) to determine which one was better patterned lob and indirect lob. In accordance with this background, this research is experimental. This type of research is quantitative, with a Two Group Pretest Posttest design. The population in this study athletes PB Lindu Aji Ngaliyan, amounting to 53 people and a sample of 20 people. In taking the sample using purposive sampling technique. There were 2 types of variables studied in this study, namely patterned lob training and indirect lob as the independent variable and the accuracy of the lob as the dependent variable. The research instrument used the lob punch test. Furthermore, the data obtained was then entered into SPSS. This research shows. the results of the Independent Sample T-Test hypothesis test obtained the value of tcount (2.182) and the value of Sig. Thus you can do patterned lob training and give indirect lob gives better results for the accuracy of the lob stroke is the pattern lob rolling exercise. The conclusions of this study are (1) there is an effect of patterned lob training on increasing lob accuracy (2) there is an effect of indirect lob training on increasing lob accuracy (3) there is a difference between the effect of patterned lob strokes and indirect lob in accuracy. The lob stroke and patterned lob training method were better than the indirect lob training method in increasing the accuracy of the lob stroke. Suggestions in this research (1) For novice athletes to continue to strive to improve the accuracy of lob strokes (2) For coaches to always provide an effective and efficient training program to their athletes, especially training programs to improve the accuracy of lob strokes, namely by providing lob stroke training. patterned (3) For further researchers, it is necessary to add other variables so that studies that examine methods to improve the accuracy of lob hits are wider.